Advanced ceramics for energy storage, thermoelectrics and photonics - Cao, Peng (Associate Professor, University of Auckland); Chen, Zhi-Gang; Xia, Zhiguo (Elsevier series on advanced ceramic materials., 2023)
Advanced Ceramics for Energy Storage, Thermoelectrics and Photonics describes recent progress in ceramic synthesis and applications in the areas of rechargeable batteries, capacitors, fuel cells, ferroelectrics, thermoelectrics, and inorganic luminescence materials. Both fundamental scientific advancements and technological breakthroughs in terms of new ceramic chemistries, new synthesis methodologies, and new applications are discussed in detail. The latest developments in advanced electrodes, ionic conductors, catalysts, thermoelectric ceramics, and luminescent powders/ceramics and their applications are also covered. With its focus on energy-related applications, the book will be a valuable reference resource for new researchers, academics, and postgraduate students who are interested in delving deeper into energy-related materials research, in particular, the areas of electronic and optical ceramics and their potential applications.